Diet composition and perceptions around food in individuals with Type 2 Diabetes Mellitus following a long-term low carbohydrate high fat diet - Murphy, Tamzyn (Department of Human Biology, 2020)
Background: Type II diabetes mellitus (T2D) is described as a progressive metabolic disease, characterised by disrupted glycaemic regulation, and is associated with high rates of morbidity and mortality. Low carbohydrate high fat (LCHF) diets may be particularly effective and sustainable for the treatment of T2D and have become a popular ‘self-therapy’. This study investigates the real-world dietary composition and potential effects of a long-term LCHF diet on T2D. Materials and Methods: A multi-method descriptive study investigating the diet and related aspects in 28 adult T2D patients perceiving to follow an LCHF diet for ≥ 6 months. Data collection included a quantitative phase (general detailed health and a food frequency (FFQ) questionnaires, 24-hour diet recall (24HR), 3-day food record, anthropometry, blood pressure, blood sampling, past medical records) and a qualitative phase (semi-structured interviews). Results: LCHF (duration 2.1 ± 1.5 y) consisted of 67% fat (143.2 ± 67.9 g, mainly saturated fat from added fat, eggs, meat, poultry, seafood and full cream dairy), 10% carbohydrate (64.0 ± 27.9 g, primarily from full cream dairy, nuts and seeds), 20 % protein (96.0 ± 37.4 g, primarily animal origin) and 3% alcohol (primarily wine). Cholesterol intake (616.3 (402.8–804.2) mg) was higher, and fibre (14.7 ± 7.5 g), calcium and folate lower than recommendations. Added sugar (0.5% of energy intake) and processed foods were seldom consumed. Daily energy intake was 1946.3 ± 807.2 kcal (436.7 ± 728.3 kcal. d-1 calculated energy deficit). Intermittent fasting (≥ 16 h. d-1) was followed by 61% of the group. From pre-LCHF to the time of the study, reductions were seen in obesity prevalence (- 50 %), body weight (- 16.9 ± 11.7 %), HbA1c concentration (- 2.45 ± 2.59 %) and T2D prevalence (36 % were no longer classified as T2D based on HbA1c and T2D pharmacotherapy). Non-pharmacologically-induced changes in HbA1c concentrations showed HbA1c reductions in 75 % of the group during the time on LCHF. LCHF was generally reported as sustainable, linked to reduced hunger and cravings and improvements in overall health and health-related quality of life (HRQoL). Challenges included constipation, initial adaptation and social difficulties related to LCHF. Discussion and conclusion: These findings are the first to describe the nature and composition of a self-selected ad libitum real-world LCHF diet and coexisting health parameters. LCHF can be sustainable in T2D patients and may be linked to improvements in glycaemic control, medication reduction, hunger, health and HRQoL.